Canada's human footprint reveals large intact areas juxtaposed against areas under immense anthropogenic pressure - Kristen Hirsh-Pearson; Chris J. Johnson; Richard Schuster; Roger D. Wheate; Oscar Venter (Canadian Science Publishing, 2022)
Efforts are underway in Canada to set aside terrestrial lands for conservation, thereby protecting them from anthropogenic pressures. Here we produce the first Canadian human footprint map by combining 12 different anthropogenic pressures and identifying intact and modified lands and ecosystems across the country. Our results showed strong spatial variation in pressures across the country, with just 18% of Canada experiencing measurable human pressure. However, some ecosystems are experiencing very high pressure, such as the Great Lakes Plains and Prairies national ecological areas that have over 75% and 56% of their areas, respectively, with a high human footprint. In contrast, the Arctic and Northern Mountains have less than 0.02% and 0.2%, respectively, of their extent under high human footprint. A validation of the final map, using random statistical sampling, resulted in a Cohen Kappa statistic of 0.91, signifying an "almost perfect" agreement between the human footprint and the validation data set. By increasing the number and accuracy of mapped pressures, our map demonstrates much more widespread pressures in Canada than were indicated by previous global mapping efforts, demonstrating the value in specific national data applications. Ecological areas with immense anthropogenic pressure highlight challenges that may arise when planning for ecologically representative protected areas.